Implementasi Kebijakan Pengelolaan Perusahaan Daerah Air Minum (PDAM) di Daerah Khusus Ibukota Jakarta - Sukma Reka Elia (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The problem PAM JAYA is the distribution of clean water. This research was conducted to find out how PAM JAYA implements its policies stated in the Special Capital Region of Jakarta Regional Regulation Number 4 of 2021 concerning Changes in the Legal Form of Regional Drinking Water Companies. The research method used is qualitative method. The focus of this research based on the Policy Implementation model proposed by Van Metern Van Horn. The results of research on Standard and Policy Target indicators show that the implementation of PAM Jaya management has been implemented, but the implementation is not optimal. In the Resource indicator, the availability of Human Resources and Financial Resources is adequate. Indicators of the Characteristics of the Implementing Organization, the division of authority and evaluation are quite optimal. In the Implementer's Attitude indicator, the implementers have understood and accepted the policy, but their attitude is still not optimal in responding to complaints. The Inter-Organizational Communication Indicator is considered to be quite optimal because PAM Jaya has optimized communication with relevant stakeholders and the community. Social, Economic and Environmental Condition Indicators are supportive, the rates set by PAM JAYA have been adjusted to the economic level of the community.